A Metabolic Signature to Monitor Endothelial Cell Differentiation, Activation, and Vascular Organization - Lopes-Coelho, Filipa (2022)
Funding: The institutions are funded by Fundação para a Ciência e Tecnologia, Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020), MOSTMICRO-ITQB (UIDB/04612/2020 and UIDP/04612/2020), and the Associated Laboratory LS4FUTURE (LA/P/0087/2020). Filipa Lopes-Coelho’s fellowship was funded by FCT (PD/BD/128337/2017). Luis G. Gonçalves was financed by an FCT contract according to DL57/2016 (SFRH/BPD/111100/2015). This work benefited from access to CERMAX, ITQB NOVA, Oeiras, Portugal, with equipment funded by FCT, project AAC 01/SAICT/2016.